Applicability of bolton's tooth size ratios in mediterranean, japanese and japanese-brazilian populations - Karine Laskos Sakoda; Arnaldo Pinzan; Guilherme Janson; Sérgio Elias Neves Cury (Universidade Estadual de Campinas, 2017)
Objective: The aim of this study was to determine if Bolton's tooth size ratios can be applied to Mediterranean, Japanese and Japanese-Brazilian populations. Materials and methods: The sample comprised 90 pairs of dental casts of untreated individuals with normal occlusion, divided into 3 groups according to ethnical characteristics: White (30 Mediterranean descendant subjects, with a mean age of 13.64 years), Japanese (30 subjects with Japanese ancestry, with a mean age of 15.63 years)  and Japanese-Brazilian (30 Japanese-Brazilian subjects, with a mean age of 13.96 years). A digital caliper was used to measure the maxillary and mandibular mesiodistal widths from first molar to first molar on each dental cast. The anterior and overall tooth size ratios were calculated. T test was applied for comparisons between Bolton standards and the ethnical groups for anterior and overall ratios. Results: Only the Japanese-Brazilian group showed significantly greater ratios than Bolton standards. Conclusion: It was concluded that Bolton's ratios are not applicable to the Japanese-Brazilian population. Therefore, it is suggested that Bolton's ratios may not be suitable for different populations.